Pengaruh Work Life Balance, Burnout, dan Motivasi terhadap Kepuasan Kerja Karyawan Bagian Produksi PG Kedawoeng Kabupaten Pasuruan - Nur Khalimah; Sri Hastari; Vita Fibriyani; Nurul Akramiah (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
The rapid development of technology accompanied by increasing industrial competition makes human resources a determining factor for organizational success. In this context, job satisfaction is an important indicator because it is closely related to individual welfare and employee productivity. This study aims to analyze the influence of work life balance, burnout, and motivation on the job satisfaction of employees in the production department of PG Kedawoeng PT Sinergi Gula Nusantara, Pasuruan Regency. This study uses a quantitative approach. The study population includes all permanent employees of the production department as many as 64 people, with census sampling techniques so that the entire population is used as respondents. Data analysis was carried out using multiple linear regression. The results showed that simultaneously work life balance, burnout, and motivation had a significant effect on job satisfaction (p=0.000; Adjusted R²=81.1%). Partially, work-life balance had no significant effect (p=0.386), burnout had a negative but insignificant effect (p=0.082), while motivation had a significant positive effect on job satisfaction (p=0.000). The motivation variable was the most dominant factor with a contribution of 76.1%, followed by burnout at 6.0% and work life balance at 0.6%.